The M-ANNHEIM classification of chronic pancreatitis: introduction of a unifying classification system based on a review of previous classifications of the disease - Schneider, Alexander; Löhr, J.-Matthias; Singer, Manfred V. (Journal of gastroenterology, 2007)
Several classification systems of chronic pancreatitis have been proposed to provide a basis for treatment and research. All of these previous classifications were designed at the height of pancreatic research of their respective times; thus, each represented the most current knowledge available to pancreatologists at the time. However, none of these classifications provide simultaneously a simple standardized system for the clinical classification of chronic pancreatitis according to etiology, clinical stage, and severity of the disease, nor are they consistently useful for directing clinical practice and comparing interinstitutional data. Thus, we aimed to develop a new classification system of chronic pancreatitis to provide a framework for studying the interaction of various risk factors on the course of the disease.